Occupational stress levels among indonesian nurses and midwives in Saudi Arabian healthcare settings: a comparative cross-sectional study - Fahruddin, Akhir; Slametiningsih, Slametiningsih; Setyorini, Dwi; Gusrina, Sylvia (Jurnal Ners, 2025)
Introduction: This study aimed to assess the occupational stress levels among Indonesian nurses and midwives working in Saudi Arabian healthcare settings. Methods: This cross-sectional comparative study assessed occupational stress among Indonesian nurses and midwives working in Saudi Arabia using the Expanded Nursing Stress Scale (ENSS). A total of 166 respondents (85 nurses and 81 midwives) completed the survey from a professional WhatsApp group. A convenience sampling was attempted, and only those who voluntarily responded to the questionnaire were included. The primary dependent variable was occupational stress, while the independent variables included profession (nurse and midwife), age, sex, education level, workplace setting, marital status, and years of experience. The analytical tests used were Mann-Whitney and Kruskal-Wallis. Results: Occupational stress among nurses (Mean = 109) and midwives (Mean = 107) was low in psychological, physical, and social environments. Workload was the most stressful factor for both nurses (Mean = 20.44) and midwives (Mean = 18.88). We found a significant difference in the level of stress based on their workplace (p = 0.038) and educational background (p = 0.005). There was no difference in the level of stress between nurses and midwives (p = 0.188). Conclusions: In comparison, either nurses or midwives have a low level of occupational stress, which is related to psychological, physical, and social environments based on ENSS tools. Therefore, optimal healthcare management and policy should be maintained and improved for migrant nurses and midwives to foster better, sustainable healthcare development in the future.